Impact of an Accelerated Pretreatment Evaluation on Linkage-to-Care for Hepatitis C-infected Persons Who Inject Drugs - Valérie Martel-Laferrière; Suzanne Brissette; Claire Wartelle-Bladou; Louis-Christophe Juteau; Maria Popa; Marie-Ève Goyer; Julie Bruneau (SAGE Publishing, 2022)
Background: Historically, hepatitis C virus (HCV) pretreatment evaluation has required multiple visits, frequently resulting in loss to follow-up and a delayed initiation of treatment. New technologies can accelerate this process. We investigated the feasibility of a single-day evaluation program and its impact on evaluation completion, treatment eligibility awareness, and treatment initiation among people who inject drugs (PWIDs). Methods: HCV-infected PWID who were unaware if they were eligible for treatment were recruited in a prospective evaluation of an accelerated model of care between 2017 and 2019 and compared to a historical cohort. The patients underwent a medical evaluation, rapid HCV viral load testing, and transient elastography during a single visit, at the end of which they were informed whether they were eligible for treatment. A historical cohort of patients fulfilling the same inclusion criteria and evaluated with the usual standard of care spanning several visits who were examined at the addiction medicine clinic from 2014 to 2016 served as the comparison group. Results: The accelerated and historical cohorts included 99 and 76 patients, respectively. The cohorts did not differ significantly by age and gender, but more patients in the historical cohort were undergoing opioid agonist therapy, while more patients in the accelerated cohort injected drugs in the last month. An accelerated evaluation resulted in a higher rate of evaluation completion (100% vs 67.1%; P  < .001). Among those eligible for treatment, the proportion of those initiating treatment was similar between the groups (51/64 (79.7%) vs. 26/37 (70.3%); P  = .28). The delay in the initiation of treatment was shorter in the accelerated cohort than in the historical cohort (69 (IQR: 49-106) days vs. 219 (IQR: 141-416) days; P  < .001). Conclusions: Accelerated evaluation enhanced the awareness of eligibility and reduced the time to initiation among eligible patients. Trial Registration: This study is registered on www.clinicaltrials.gov (NCT02755402).